Need Assessment for Developing a Culturally Adapted Interactive Workbook to Manage Academic Stress in School Counseling - Noorlaila, Feida; Arumsari, Cucu; Nugraha, Agung; Effendi, Merlin (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to conduct a needs assessment as the basis for developing an interactive workbook for academic stress management within school counseling services. Methodology: This study employed a Research and Development approach using the ADDIE model, limited to the analysis phase. A mixed-method design was applied to obtain comprehensive data. Quantitative data were collected through a questionnaire administered to 169 students, while qualitative data were obtained through in-depth interviews with 10 students and one school counselor, as well as classroom observations. The instruments included the Academic Stress Scale (34 items, α = 0.918) and semi-structured interview guidelines. Quantitative data were analyzed descriptively and inferentially using ANOVA and Pearson correlation, while qualitative data were analyzed through thematic analysis. Main Findings: The findings indicate that academic stress among students is relatively high, with 91.3% of participants experiencing moderate to high levels of stress. The primary sources of stress include examination pressure (60%), social conflicts (25%), and family expectations (15%). Students expressed strong preferences for counseling media that are visual, simple, culturally relevant, and usable independently. In particular, students preferred workbook-based media integrating local cultural values such as cooperation (gotong royong) and Islamic spirituality. Novelty/Originality of this study: This study highlights the urgent need for culturally adapted counseling media to support students’ emotional regulation and stress management. The novelty of this study lies in integrating the needs assessment of academic stress with cultural adaptation of Dialectical Behavior Therapy principles into an interactive workbook format suitable for school counseling.